2021
DOI: 10.3389/fcell.2021.639691
|View full text |Cite
|
Sign up to set email alerts
|

Mogroside V Protects Porcine Oocytes From Lipopolysaccharide-Induced Meiotic Defects

Abstract: Accumulating evidence has demonstrated that lipopolysaccharide (LPS) compromises female reproduction, especially oocyte maturation and competence. However, methods to protect oocyte quality from LPS-induced deterioration remain largely unexplored. We previously found that mogroside V (MV) can promote oocyte maturation and embryonic development. However, whether MV can alleviate the adverse effects of LPS exposure on oocyte maturation is unclear. Thus, in this study, we used porcine oocytes as a model to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…As expected, we further found that MV treatment improved the proportion of 2-cell embryos and blastocysts in BaP-exposed mice. In addition, previous studies have demonstrated that MV can improve porcine oocyte in vitro maturation and protect oocytes from quality deterioration induced by postovulatory ageing or LPS exposure (Nie et al, 2019;Nie et al, 2020;Yan et al, 2021). As subsequent embryonic development potential is an indicator of oocyte cytoplasmic maturation, our findings show that MV might alleviate the deterioration of oocyte cytoplasmic maturation induced by BaP exposure.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…As expected, we further found that MV treatment improved the proportion of 2-cell embryos and blastocysts in BaP-exposed mice. In addition, previous studies have demonstrated that MV can improve porcine oocyte in vitro maturation and protect oocytes from quality deterioration induced by postovulatory ageing or LPS exposure (Nie et al, 2019;Nie et al, 2020;Yan et al, 2021). As subsequent embryonic development potential is an indicator of oocyte cytoplasmic maturation, our findings show that MV might alleviate the deterioration of oocyte cytoplasmic maturation induced by BaP exposure.…”
Section: Discussionsupporting
confidence: 66%
“…In vitro studies have demonstrated that MV can alleviate lipopolysaccharide-induced inflammation in cultured cells (Li et al, 2019;Liu et al, 2021). Moreover, we found that MV supplementation in vitro maturation medium can promote porcine oocyte maturation (Nie et al, 2020), alleviate the quality deterioration of in vitro ageing oocytes (Nie et al, 2019), and protect porcine oocytes from meiotic defects induced by LPS (Yan et al, 2021). Due to its beneficial effects on oocyte maturation and competence, we speculate that MV can protect oocytes from meiotic defects caused by BaP exposure.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations